2018
DOI: 10.1177/0961463x17752282
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ subjective well-being: The role of adolescents’ and mothers’ time perspectives

Abstract: This study investigated the relations between adolescents’ and their mothers’ time perspectives and adolescents’ subjective well-being. The sample included 104 adolescents (72.1% girls), aged between 15 and 17 years and their mothers ( M = 42.67, SD = 5.66). Adolescents completed scales measuring their life events, time perspective, depressive symptoms and life satisfaction. Mothers also fill in a scale assessing their time perspective. The results showed that adolescents who reported higher levels of negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
(130 reference statements)
1
3
0
1
Order By: Relevance
“…Overall, our results show that exposure to NLEs are important to consider when discussing and understanding the occurrence of mental health problems among Romanian adolescents, thus contributing to the existing literature. Regarding the association between NLEs and internalizing problems and in line with other studies (Grant et al, 2004, 2014; Raknes et al, 2017b), our results showed that those adolescents who reported experiencing specific negative events also reported more depressive and anxiety symptoms, thus, supporting the claim that the occurrence of adversities is a risk factor for negative mental health outcomes Braboy Jackson & Finney, 2002; Dinya et al, 2009; Dovran et al, 2019; Măirean and Diaconu–Gherasim, 2018). Proximity of NLEs had a little effect on reported depression, but it had a greater impact on anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our results show that exposure to NLEs are important to consider when discussing and understanding the occurrence of mental health problems among Romanian adolescents, thus contributing to the existing literature. Regarding the association between NLEs and internalizing problems and in line with other studies (Grant et al, 2004, 2014; Raknes et al, 2017b), our results showed that those adolescents who reported experiencing specific negative events also reported more depressive and anxiety symptoms, thus, supporting the claim that the occurrence of adversities is a risk factor for negative mental health outcomes Braboy Jackson & Finney, 2002; Dinya et al, 2009; Dovran et al, 2019; Măirean and Diaconu–Gherasim, 2018). Proximity of NLEs had a little effect on reported depression, but it had a greater impact on anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Romanian adapted form (Măirean & Diaconu-Gherasim, 2019 ) of the Time Perspective Inventory (S-ZTPI; Carelli et al 2011 ) was used to evaluate the participants’ experience of time. The S-ZTPI consists of 64 items and measure six distinct subscales: Past Positive (9 items, e.g., I enjoy stories about how things used to be in the good old times , α = 0.75), Past Negative (10 items, e.g., Painful past experiences keep being replayed in my mind , α = 0.80), Present Hedonistic (15 items, e.g., I make decisions on the spur of the moment , α = 0.76), Present Fatalistic (9 items, e.g., My life path is controlled by forces I cannot influence , α = 0.71), Future Positive (11 items, e.g., When I want to achieve something, I set goals and consider specific means for reaching those goals , α = 0.68), and Future Negative (10 items, e.g., Usually, I do not know how I will be able to fulfill my goals in life , α = 0.66).…”
Section: Methodsmentioning
confidence: 99%
“…Total scores were computed by averaging items for each subscale. The scale has good validity in various cultural samples (e.g., Măirean & Diaconu-Gherasim, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Эти оценки субъективны, но, независимо от этого, они могут оказывать благоприятное и неблагоприятное воздействие на психологическое благополучие в целом или его отдельные компоненты (Tseferidi et al, 2017). Негативное восприятие прошлого, как правило, отрицательно сказывается на психологическом благополучии молодых людей, может вызывать депрессивные симптомы, в то время как позитивная оценка прошлого имеет обратный эффект (Măirean, Diaconu-Gherasim, 2019;Chen et al, 2021). Некоторые исследования показывают, что интенсивность связей временнóй перспективы и показателей, близких к психологическому благополучию, например счастья, с возрастом ослабевает (Simons et al, 2018).…”
Section: Introductionunclassified